Efektifitas Berbagai Macam Zat Pengatur Tumbuh (ZPT) pada Konsentrasi yang Berbeda Terhadap Pertumbuhan serta Rasio Shoot/Root Stek Mawar (Rosa sp.) - Tiara Alfionita; Nurhidayati Nurhidayati; Mahayu Woro Lestari (AGRONISMA, 2019)
This study aims to determine the effect of various kinds of Plant Growth Regulator (PGR) (rootone-f, red onion extract and coconut water) with different concentration on growth and shoot/root ratio on rose cuttings. The design used was Randomized Block design (RBD) (R, the treatment (Z1 = PGR rootone-f; Z2 = PGR red onion extract; Z3 = PGR coconut water; K1 = 50%; K2 = 75%; K3 = 100%) plus control. The results showed that the treatment of Z2K3 had an average variable growth in the number of shoots of 2.78, shoot length of 1.39 cm, number of leaves as much as 4.52 strands, root length of 346.97 cm, fresh weight of shoot biomass of 2.33 g, fresh weight of root biomass of 1.19 g, fresh weight of total biomass of 3.51 g, dry weight of total biomass of 1.07 g better than all treatments. For dry shoot biomass weight at Z1K3 treatment of 0.84 g, dry weight of root biomass at Z1K1 treatment was 0.45 g and shoot / root ratio in Z3K3 treatment was 11.34.Key words: Rose, shoot/root ratio, cuttings, PGR